Efecto de sales de boro en la densidad y en el módulo de elasticidad de tres maderas mexicanas - Sotomayor-Castellanos, Javier-Ramón (Universidad de Costa Rica, 2018)
The species Guazuma ulmifolia, Spathodea campanulata and Abies religiosa have potential for the fabrication of wood products with benefit. However, there is no information about its properties regarding the retention of protection substances, neither of its possible effect on the wood density and the modulus of elasticity. The research aimed to analyze, in samples of on the density a G. ulmifolia, S. campanulata and A. religiosa wood, the effect of the hot-cold bath of the boron salts nd the modulus of elasticity. Before and after the treatment, the wood density, the modulus of elasticity, and the retention of boron salts were established. Differences-of-means tests between the species were performed, and after the treatment an analysis of variance was carried for the variable retention. In the specimens of G. ulmifolia, S. campanulata y A. religiosawood, the retention of boron salts was different for each one of them. After the application of the salts, the density of G. ulmifolia y A. religiosa increased, and decreased in S. campanulata. The boron salts did not modify the modulus of elasticity of the wood for the three species.